Fast Exfoliation and Functionalisation of Two‐Dimensional Crystalline Carbon Nitride by Framework Charging. (29th August 2018) - Jia, Jingjing; White, Edward R.; Clancy, Adam J.; Rubio, Noelia; Suter, Theo; Miller, Thomas S.; McColl, Kit; McMillan, Paul F.; Brázdová, Veronika; Corà, Furio; Howard, Christopher A.; Law, Robert V.; et al.
Abstract: Two‐dimensional (2D) layered graphitic carbon nitride (gCN) nanosheets offer intriguing electronic and chemical properties. However, the exfoliation and functionalisation of gCN for specific applications remain challenging. We report a scalable one‐pot reductive method to produce solutions of single‐ and few‐layer 2D gCN nanosheets with excellent stability in a high mass yield (35 %) from polytriazine imide. High‐resolution imaging confirmed the intact crystalline structure and identified an AB stacking for gCN layers. The charge allows deliberate organic functionalisation of dissolved gCN, providing a general route to adjust their properties.